Rapid bark-mediated tree stem methane transport occurs independently of the transpiration stream in Melaleuca quinquenervia - Jeffrey, Luke C (The New phytologist, 2024)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.